Cancer incidence over the last decade in Omsk and Orenburg regions: a descriptive study - N. G. Shirlina; A. S. Vyaltsin; V. L. Stasenko; A. V. Klimushkin (Фундаментальная и клиническая медицина, 2020)
Aim. To assess the incidence of malignancies in Omsk and Orenburg Regions.Materials and Methods. We analyzed statistical reports (form # 7) from health authorities of Omsk and Orenburg Regions which contain the data on cancer incidence in the population during the last decade (2009-2018).Results. The incidence of malignancies in Omsk and Orenburg Regions had a moderate upward trend. Cancer incidence in the urban population of Orenburg region was higher than in the corresponding rural population, with the opposite ratio in the Omsk region. Average long-term standardized incidence rate of malignancies in Omsk and Orenburg regions was 276,5 0/0000 and 273,0 0/0000, respectively. Cancer incidence prevailed among the male population regardless of the indicator type. The prevalence of males across all patients was 46.0% and 46.8% in Omsk and Orenburg Region, respectively.Conclusion. Average long-term indicators of cancer incidence in Orenburg and Omsk Regions do not differ; however, different incidence pattern was detected in urban and rural populations in these regions over the decade.